230k views
1 vote
D

Question 4
Using the same algorithm:
• Start with a number and add 2 to it.
• Double the result.
• Subtract 3 from that quantity.
Which function represents the inverse of the above algorithm?

User Smilez
by
5.0k points

1 Answer

2 votes

First find function


\\ \bull\tt\dashrightarrow f(x)=2(x+3)-3


\\ \bull\tt\dashrightarrow f(x)=2x+6-3


\\ \bull\tt\dashrightarrow f(x)=2x+3

Now


\\ \bull\tt\dashrightarrow y=2x+3


\\ \bull\tt\dashrightarrow x=(y-3)/(2)

But


\\ \bull\tt\dashrightarrow y=f(x)


\\ \bull\tt\dashrightarrow x=f^(-1)(y)

Hence

.


\\ \bull\tt\dashrightarrow f^(-1)y=(y-3)/(2)

Replace y by x


\\ \bull\tt\dashrightarrow f^(-1)(x)=(x-3)/(2)

User SharkofMirkwood
by
5.3k points